1981
DOI: 10.1002/qua.560200205
|View full text |Cite
|
Sign up to set email alerts
|

Potential energy curves in complementary base pairs and in model hydrogen bonded systems

Abstract: The potential energy curves for the intermolecular proton transfer in complementary base pairs and respective hydrogen bonded model systems have been studied at the semiempirical all-valence and ab inirio STO-3G level. The proton transfer probability was found to be markedly greater in excited electronic states than that of the ground state. Substantial lowering of the potential barrier height for the coupled double proton transfer in model (HCOOH)2 system has been obsehed when the dynamics of zero-point vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
5

Year Published

1984
1984
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 23 publications
1
1
0
5
Order By: Relevance
“…Zielinski et al [20] have shown that in order to obtain reliable numerical data on either the tautomerization barrier or the energy difference between the tautomeric forms, geometry relaxation is needed. In the formic acid dimer, a relaxation of the heavy atoms resulted in deeper wells (more so for the tautomeric form) and a lowering of the potential barrier [22]. Similar effects would be expected for the results presented here on the Guanine-Cytosine base pair.…”
Section: Discussionsupporting
confidence: 77%
“…Zielinski et al [20] have shown that in order to obtain reliable numerical data on either the tautomerization barrier or the energy difference between the tautomeric forms, geometry relaxation is needed. In the formic acid dimer, a relaxation of the heavy atoms resulted in deeper wells (more so for the tautomeric form) and a lowering of the potential barrier [22]. Similar effects would be expected for the results presented here on the Guanine-Cytosine base pair.…”
Section: Discussionsupporting
confidence: 77%
“…The most representative constituent of the interaction energy for polar molecules is the electrostatic term which outside the van der Waals volume is dominated by the multipole contribution q b E C may be satisfactorily approximated within the difference molecular electrostatic potential approach [7]. Moreover, from the difference electrostatic molecular potential map, one may visualize the optimal charge distribution of the catalytic environment [7,8] and predict at least qualitatively the catalytic or inhibitory action on any neighboring molecule. Such an approach is described elsewhere in detail [7] and may constitute a reasonable initial step in a search for the optimal arrangement of the molecular environment within a more rigorous approach.…”
Section: Methodsmentioning
confidence: 99%
“…Кроме того, во всех рассмотренных Каталаном и Перезом случаях [19] Прежние изучения [21,22] показали взаимо связь между движением протонов и деформацион ным движением остова тяжелых ядер димера, кото рая в основном изменяет расстояние между моно мерами. Поэтому мы провели такие же расчеты потенциальных кривых, где при оптимизации гео метрии условие R(N,-H) + R(H...N 7 ) = 3 А было удалено.…”
unclassified
“…Как уже указывалось, двухпротонная фототау томерия была предложена [1 ] в качестве механиз ма индуцирования мутаций в ДНК с помощью УФ-света. Это предположение обсуждалось как возможное и в последующих работах [4, 19,22]. Между тем, соответствующие франк-кондоновские потенциальные кривые Н-связей для пар основа ний ДНК, вычисленные нами [28,29], не привели к изменению асимметрии потенциальных кривых в состоянии Sj и, следовательно, не подтверждают…”
unclassified
See 1 more Smart Citation